Pengaruh Debt To Equity Ratio dan Return On Assets Terhadap Nilai Perusahaan pada Perusahaan Subsektor Perbankan Yang Terdaftar di Bursa Efek Indonesia Periode 2017-2024 - Novia Anggelina; Kenedi Kenedi; Furtasan Ali Yusuf (Pusat Riset dan Inovasi Nasional, 2025)
Company value is a key indicator reflecting investor confidence in a firm's future prospects. In the banking sector, which operates under strict regulatory frameworks and high risk exposure, the choice of capital structure and the efficiency of asset utilization are critical factors influencing market valuation. Over the period 2017–2024, fluctuations in the Price to Book Value (PBV), Debt to Equity Ratio (DER), and Return on Assets (ROA) among banking companies listed on the Indonesia Stock Exchange (IDX) have presented notable dynamics warranting further examination. This study aims to analyze the partial and simultaneous effects of DER and ROA on company value, as measured by PBV, within the banking sub-sector. Employing a quantitative research design, panel data from four banking companies—selected through purposive sampling—were analyzed. The study utilized panel data regression, with the most appropriate model determined via Chow, Hausman, and Lagrange Multiplier tests. Classical assumption testing and descriptive statistical analysis were also conducted to ensure robustness. The findings indicate that ROA has a significant positive impact on company value, demonstrating the importance of profitability in enhancing market valuation. In contrast, DER exhibits a significant negative partial effect, suggesting that higher leverage may erode investor confidence and depress valuation. Simultaneously, DER and ROA jointly exert a significant influence on PBV, confirming that both profitability and capital structure are integral to shaping firm value in the banking sector. The study concludes that profitability plays a dominant role in improving company value, while capital structure must be strategically managed to optimize its contribution to market perception. These results offer practical implications for banking management, highlighting the need to maintain healthy profitability levels while carefully balancing debt usage to achieve sustainable growth in firm value.